Physical exercises to improve the stability of the target sight in sport shooting - Mercedes Miló Dubé; David Abreu Morejón; Yoandry Piñeiro Febles (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
Sport shooting stands for a highly technical sport, and a competitive art. It is the target sight one of the more important technical elements because it favors the sport performance and it must be considered in the training sessions from the junior school categories. This research meets the goals of proposing a set of physical exercises to improve the stability of the target sight technique for the Shooting athletes, category 13-16, field Standard gun pistol in the Sport School "Ormani Arenado Llonch" in Pinar del Río, Cuba. To fulfill this objective it was applied scientific observation, surveys and interviews, theoretical methods were also used in this research adjusted to 11 athletes and 3 coaches as the sample of research belonging to this school under study. Based on the diagnosed weaknesses found along the training was selected a set of physical exercise to improve the target sight empowering the pedagogical implication and without breaking the planning process of the sport.